Identità, ruolo, infrazione di ruolo nella ʻscenaʼ della vita Riflessioni su Pirandello e Goffman - Scozzafava, Angela; Valchera, Caterina (B@belonline, 2020)
The paper aims to clarify and deepen the most recognized aspects, in literature of a comparison between Pirandello and Goffman, starting from the indications given by the sociologist. We focused on Goffman’s main ideas with particular attention to The Presentation of Self in Everyday Life and Frame Analysis: an Essay on the Organization of Experience. The excerpts chosen among the wide Pirandello’s production are the most suitable ones for this type of comparison, and also the ones which best highlight ideological and cultural differences. The essence of our argument is indeed focused on the will of drawing out the ʻuniqueness’ of the sociologist’s beliefs compared to those of the italian ʻphilosopher-writerʼ, considering their peculiar visions of the world, man and society.